Preservice teachers’ teaching internship affects professional identity: Self-efficacy and learning engagement as mediators - Cai, Zhiling; Zhu, Jinxing; Tian, Saiqi (Frontiers in Psychology, 2022)
The purpose of this study is to investigate the roles that self-efficacy and learning engagement play in the relationship between preservice teachers' professional identities and their teaching internship experiences. The study involved 309 preservice teachers in total, and the variables were measured using questionnaires. For the data analysis, we used structural equation modeling. The study's findings showed that (a) teaching internship, professional identity, self-efficacy, and learning engagement were all significantly correlated with one another; (b) both self-efficacy and learning engagement partially mediated the relationship between teaching internship and professional identity in a parallel manner; and (c) self-efficacy and learning engagement also sequentially mediated the relationship between teaching internship and professional identity.